Fitness for life health-optimizing physical education series for senior high school - Porto, Jerome A.; Vargas, Aida A.; Collao, Mia Elaine P. (Health-optimizing physical education series for senior high school, 2016)
"The Health Optimizing Physical Education (HOPE) series for senior high school utilizes experiential learning approaches ageappropriate concepts and interesting activities to help students improve their fitness health and wellbeing as individuals and productive citizens of the society It aims to educate students on fitness sports dance and recreation for life which are essentials to optimum and lifelong health and wellness" -- Preface.